Pengaruh Pasar Modern Terhadap Pendapatan Pedagang Pasar Tradisonal - Sunarti Djoko (Peneliti.net, 2020)
Modern markets and traditional markets are both places where producers and consumers meet to meet their needs but in different ways, for example modern markets are in the form of hapymarts, malls and supermarkets while traditional markets are in the form of tents, figures and kiosks. Quantitative research was used in the form of questionnaires in data collection. . The population in this study were all traditional (hygienic) market traders in Ternate, namely 413 traders. Sampling was carried out using the area sampling method and the number of samples was 40 respondents. Subjects are hygienic market traders with several types of traders, namely fish traders, meat traders, basic food traders, restaurant traders and clothing traders. The results of this study indicate that through the SPSS 16 test results there is an influence between modern markets (X) on the income of traditional market traders (Y) as seen in the R Square test results of 0.30. This shows the level of a strong relationship between the dependent and independent variables that is equal to 30%. While the remaining 70% is influenced by other indicators not examined in this study.